Ceci n'est pas la mort: Evidence for the recruitment of self‐reference from surrealistic art under mortality salience. (6th December 2014) - Silveira, Sarita; Gutyrchik, Evgeny; Wetherell, Geoffrey; Bao, Yan; Pöppel, Ernst; Blautzik, Janusch; Reiser, Maximilian; Frey, Dieter; Graupmann, Verena
Abstract: Previous research has demonstrated that death reminders influence how we perceive art. In the context of terror management theory, this has been explained by the death‐transcending quality of art to convey cultural meaning. In two studies, we examined psychological and neurocognitive responses to naturalistic and surrealistic art when death was primed. We found that naturalistic paintings were evaluated similarly in terms of personal reassurance in both mortality salience and control condition, whereas surrealistic paintings were evaluated as more reassuring in the mortality salience condition than in the control condition. Using high‐field functional magnetic resonance imaging in a second study, we found a similar pattern of results, showing specific activation in the precuneus, a brain area associated with self‐related operations, in all prime conditions for the viewing of naturalistic paintings, but only in the death and disgust prime conditions when viewing surrealistic paintings. Our results suggest motivated self‐reference when viewing both naturalistic and surrealistic artworks under mortality salience. Copyright © 2014 John Wiley & Sons, Ltd.